Implementasi Metode 4DX dalam Meningkatkan Akurasi Stock pada PT. X - Yohana Kania Partadarsana; Indarto; Paulus Wardoyo (Commodities, Journal of Economic and Business, 2026)
This research will explore the impact of implementing the 4DX method, the obstacles experienced, and the efforts made in overcoming obstacles to improve stock accuracy. This research method uses a qualitative approach conducted during one 4DX period. The qualitative method implemented is based on phenomenology. Data collection through interviews and direct observation. Through this method will explore what factors can affect stock accuracy based on 4 factors: focus on goals, identify and overcome obstacles, measure results, and accountability rhythm. The research conducted at PT X provides results that stock control is a staple in the manufacturing industry because it is related to the continuity of the production process. In an effort to improve stock accuracy through the 4DX method requires a computerized documented process and competent operators are needed in their fields. In addition, it is also necessary to have disciplined recording and soft skills owned by employees as a means of encouraging the achievement of company goals. So that in this study the implementation of the 4DX method can affect the improvement of stock accuracy with a result of 99.12%.